ANALISIS PENGARUH KUALITAS LAYANAN, ATRIBUT PRODUK DAN LOKASI TOKO TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP MINAT BELI ULANG PADA BUTIK STAGE MY FASHION DI NGALIYAN SEMARANG - Ariyani, Yunita Endah; Dirgantara, I Made Bayu (Diponegoro Journal of Management, 2018)
The current retail business especially in clothing boutiques, is increasingly causing intense competition among boutique owners. The purpose of this study is to determine the effect of service quality, product attributes and store location to customer satisfaction and its impact on repurchase intention at Stage My Fashion boutique.This research uses non probability sampling technique with purposive sampling method. The samples in this study were 150 respondents. The population of the study was all consumers who had ever done purchase transaction at Stage My Fashion boutique. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument. The results of this study indicate that product attributes, store location, service quality has a positive and significant impact on customer satisfaction, customer satisfaction also have a positive and significant effect on the repurchase intention.